The role of behaviour in vulnerability to air pollution—a framework and evidence review - Antonio Avila-Uribe; Anomitro Chatterjee; Daire McCoy; Ganga Shreedhar (Frontiers in Environmental Health, 2026)
Air pollution remains a major environmental health challenge, imposing wide-ranging burdens on populations in high- and middle-income countries where it remains a policy-relevant problem. Despite this, existing frameworks for understanding who is most affected, and why, rarely account for the behavioural mechanisms that shape individual vulnerability. This review paper proposes a framework to describe vulnerability to air pollution and situates the role of behaviour in the pathway from pollution to individual outcomes. We consider a broad definition of vulnerability, comprised of three interrelated dimensions: exposure (pollutant concentration encountered by an individual), susceptibility (how much an individual’s well-being is harmed given their exposure), and adaptation (actions taken to reduce exposure or susceptibility). We use this framework to structure a narrative review of multi-disciplinary evidence, touching on a broad set of impacts from physical and mental health to economic outcomes. We show how adaptation behaviour can moderate the relationship between pollution and impacts, while behavioural choices like heating, cooking and ventilation mediate that relationship. Finally, we discuss important overlaps across dimensions of vulnerability, where some components reinforce or attenuate the impacts of others.